A cytosine methyltransferase ortholog dmtA is involved in the sensitivity of Aspergillus flavus to environmental stresses. Issue 5 (May 2017) - Zhi, Qing-Qing; Li, Jie-Ying; Liu, Qiu-Yun; He, Zhu-Mei
Abstract: DNA methylation is an important epigenetic modification that depends on DNA methyltransferases (DMT). However, the filamentous fungus Aspergillus flavus has no detectable methylation, and role of a DMT homologue, DmtA, is undefined. Here we describe the role of the dmtA gene responding to changes in the environment by comparing knockout, point mutation, over-expression and wild type strains. Deletion of dmtA differentially affected conidia development in a media-dependent fashion, which suggests that dmtA plays an important role in conidiation. Furthermore, ΔdmtA strains lost the capacity to form the resistant structure, sclerotia, and alleviated sensitivity to several stress conditions, such as high osmotic pressure, hypoxia, low water activity and a high calcium concentration. We also noticed that deletion of dmtA and mutation C377S in DmtA negatively affected aflatoxin production and down regulated the expression of some early ( fas-1, pksA, nor-1 ), middle and late ( nor-A, ver-1, avnA, omtB ) genes in the aflatoxin biosynthetic cluster. Finally, we found that all tested strains showed a similar phenotype when treated with 5-azacytidine. Our results indicate that the dmtA gene is important in regulation of aflatoxin biosynthesis and for A. flavus to adapt to stressful environments and for survival, although it may hold no apparent function in DNA methylation. Highlights: Deletion of dmtA affects conidia development in a media-dependent way. Deletion of dmtA leads to loss of sclerotia formation. dmtA deletion strains show alleviated sensitivity to several stress conditions. Deletion and point mutation of dmtA leads to decreased AF production and low expression level of relative genes.